Clinical observations of weight stigma among nursing students: A descriptive approach - Myah Kerbyson; Kristen D. Clark (Wiley, 2024)
Abstract Background Mistreatment of individuals due to their body size or weight stigma has been described as a source of stress and as a deterrent for engagement in the healthcare system. Efforts to reduce weight stigma have included curricular interventions to reduce weight bias among future healthcare professionals. However, few studies have examined students' observations of weight stigma and subsequent socialization to healthcare environmental norms. Aims The purpose of this study is to evaluate observed weight stigma among pre‐licensure nursing students and recent graduates during clinical rotations and its effect on the perceived ability to provide respectful care to people in larger bodies. Materials and Methods A cross‐sectional, descriptive study was conducted from February to March 2023. Participants answered questions related to personal weight bias (Fat Phobia Scale), observations of weight stigma, and perceived ability to provide respectful care. Results Ninety‐one participants completed the survey, of whom half (n = 48) held a high level of weight bias. A quarter of participants (n = 23) reported that they engaged in weight stigma behaviors and a quarter (n = 24) of participants observed weight stigma behaviors from two or more healthcare professional roles. Almost one‐third (n = 10) of participants who observed weight stigma behaviors perceived that it impacted their ability to provide respectful care to patients in larger bodies. Conclusions These findings describe that weight stigma enacted by multiple healthcare professional roles is observed by nursing students during clinical rotations and is perceived to impact their ability to provide respectful care. Efforts to improve healthcare professionals' sensitivity to the effects of weight bias and weight stigma should include addressing the role of socialized norms on weight bias among future healthcare professionals.